Design of a smart lime mortar with conductive micro and nano fillers for structural health monitoring. (27th February 2023) - Drougkas, Anastasios; Sarhosis, Vasilis; Basheer, Muhammed; D'Alessandro, Antonella; Ubertini, Filippo
Abstract: Structural health monitoring is an essential tool for assessing the performance of buildings and infrastructure, especially after critical events or the application of structural interventions. When dealing with architectural heritage structures, both structural health monitoring instrumentation and intervention materials need to be as inconspicuous and unintrusive as possible, both in terms of mechanical compatibility and aesthetics. Therefore, the design of smart sensors based on construction materials used in conservation engineering promises to provide an acceptable integrated structural health monitoring and upgrading solution for historic structures. In this paper an experimental investigation of smart intervention materials for historic masonry structures is presented. The materials consisted of natural hydraulic lime mortars modified through the inclusion of electrically conductive micro- and nanofillers: graphite, carbon nanotubes and carbon microfibres. The fillers provide multifunctionality to the matrix material based on an enhancement of its piezoresistive characteristics. Further, they result in an improvement of the mechanical properties of the intervention material without compromising its mechanical and chemical compatibility with the original structure. The resulting materials were evaluated based on mechanical property improvement, piezoresistivity enhancement and ease of production.